The Radio Frequency Source Position Finder Based on The Triangle-Centroid-Algorithm - Samuel Kristiyana; Adhi Susanto; Sunarno Sunarno; Risanuri Hidayat (IJITEE (International Journal of Information Technology and Electrical Engineering), 2017)
Radio Direction Finder (RDF) had been used as a part of the system in order to  determine the direction of the Radio Frequency (RF) source. This research had used  three different RDF stations without any mobile human operator. The direction data were collected from the each RDF station, it would be calculated using the triangle-centroid-algorithm. Therefore, the RF source position had been automatically determined. This experiment result of the RF source imaginary was compared with the real RF source at about 3.2 meters for latitude, and 3.3 meters for longitude. The results of this method and experiment are very useful for scientist and engineers in application of RF engineering.